2010
DOI: 10.14411/eje.2010.068
|View full text |Cite
|
Sign up to set email alerts
|

Germ cell cluster formation and ovariole structure in Puto albicans and Crypticerya morrilli (Hemiptera: Coccinea). Phylogenetic implications

Abstract: Abstract. The organization and development of ovaries in representatives of two families (Putoidae and Monophlebidae) of scale insects are described. Developing ovaries of Puto albicans McKenzie, 1967 and Crypticerya morrilli (Cockerell, 1914) consist of numerous clusters of cystocytes that are arranged in the form of rosettes. At the end of the last nymphal instar these clusters start to protrude from the interior of the ovary into the body cavity and the ovarioles begin to be formed. The ovary of a young fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(53 citation statements)
references
References 33 publications
4
47
0
2
Order By: Relevance
“…As a consequence, in the ovaries of an adult female these bacteria are present both in trophocytes and oocytes. This mode of transmission has never been observed in other aphids but is quite common in scale insects (Buchner, 1965;Niżnik & Szklarzewicz, 2007;Szklarzewicz et al, 2010Szklarzewicz et al, , 2013. In contrast to the situation encountered in Stomaphis quercus, the third type of microorganisms was not observed in germ cells of Eulachnus rileyi.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…As a consequence, in the ovaries of an adult female these bacteria are present both in trophocytes and oocytes. This mode of transmission has never been observed in other aphids but is quite common in scale insects (Buchner, 1965;Niżnik & Szklarzewicz, 2007;Szklarzewicz et al, 2010Szklarzewicz et al, , 2013. In contrast to the situation encountered in Stomaphis quercus, the third type of microorganisms was not observed in germ cells of Eulachnus rileyi.…”
Section: Discussionmentioning
confidence: 77%
“…Extensive, histological investigations by Buchner (1965) and more recent ultrastructural studies (Cheng & Hou, 2001;Szklarzewicz & Moskal, 2001;Szklarzewicz et al, 2006Szklarzewicz et al, , 2010Szklarzewicz et al, , 2013Sacchi et al, 2008;Kuechler et al, 2010Kuechler et al, , 2011Matsuura et al, 2012;Swiatoniowska et al, 2013) have shown that during hemipteran evolution various modes of inheritance of endosymbiotic microorganisms by subsequent generations have developed. The extracellular gut bacteria that are typical of most the heteropterans so far examined (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Büning, 1985;Książkiewicz-Kapralska, 1985;Huebner, 1981;Biliński et al, 1990;Simiczyjew et al, 1998;Szklarzewicz, 1998a;Štys et al, 1998;Szklarzewicz et al, 2000Szklarzewicz et al, , 2009. In contrast to the ovarioles of other hemipterans, the ovarioles of scale insects do not possess terminal filaments and contain a small number of germ cells in each ovariole and single oocyte in the vitellarium (scale insect synapomorphies) (Książkiewicz, 1980;Szklarzewicz & Biliński, 1995;Szklarzewicz, 1997Szklarzewicz, , 1998aKoteja et al, 2003;Szklarzewicz et al, 2002Szklarzewicz et al, , 2005Szklarzewicz et al, , 2010Szklarzewicz et al, , 2013Niżnik & Szklarzewicz, 2007). It is noteworthy that their ovaries appeared to be so different from those of other hemipterans that they were formerly classified as polytrophic (Jura, 1958;Magakyan et al, 1975).…”
Section: Introductionmentioning
confidence: 99%